Association between birthweight and Acute Lymphoblastic Leukemia in children, a systematic review - Aduse-Poku, Livingstone; Akyirem, Samuel (Open Science Journal, 2020)
Background Birthweight is normally determined by a range of genetic traits and exposures occurring within the intra-uterine environment. Some epidemiological studies have reported high birthweight as a risk factor of Acute lymphoblastic Leukemia (ALL). Other studies have however not demonstrated this relationship. Objectives The objective of this review is to assess the association between birthweight and Acute Lymphoblastic Leukemia in children. Search methods We searched observational studies from Cochrane, MEDLINE, EMBASE, ISI Web of Science, BIOSIS, the allied and Complementary Medicine Database and National Research Register, ClinicalTrial.gov, WHO International Trials Registry Platform. Selection criteria We included case control and cohort studies assessing the association between birthweight and ALL in children. All particpants below the age of 18 years (children) with ALL were included in the analysis. The independent variable in this review was birthweight. Birthweight was categorised into two (2). Birthweight >4kg (experimental arm) and ≤ (control arm). Data collection and analysis Two reviewers independently assessed identified studies through two stages of screening. First, titles and abstracts of all references identified through searches were screened and irrelevant studies were excluded. Also, full texts of potentially eligible studies were further assessed according to previously defined inclusion criteria. Studies that did not meet inclusion criteria were excluded and reasons for their exclusion were stated. All studies that met the inclusion criteria were included. Areas of disagreement were resolved by a third-party review. Two review authors double checked the studies independently. Main results Out of the 348 studies screened, 16 of them met the inclusion criteria. A total of 3650728 participant provided data for analysis in this review. These studies were published between 1987 and 2018. The age span of studies was similar across studies (roughly (0-18 years). The vast majority of ALL was diagnosed before 15 years. 14 of the included studies were case control studies and 2 of them were cohort studies. Figure 1 presents odd ratio estimates for effect of birthweight on ALL (≤ 4000g vs. > 4000g). There was a statistically significant positive relationship between high birthweight (birthweight > 4000g) and risk of ALL (16 studies, OR 0.81, 95% CI 0.77, 0.85). Authors' conclusions Our study revealed a significant positive relationship between high birthweight and ALL. Several studies have demonstrated an association between factors such as: high pre-pregnancy weight and height; gestational age greater than 42 weeks; parity greater than and high birthweight. Therefore, public health programs and interventions aimed at reducing the incidence of these maternal factors can reduce the risk of high birthweight and lower the incidence of ALL.